Decreased level of psychobiological factor novelty seeking and lower intelligence in men latently infected with the protozoan parasite Toxoplasma gondii Dopamine, a missing link between schizophrenia and toxoplasmosis? - Flegr, Jaroslav; Preiss, Marek; Klose, Jirí; Havlícek, Jan; Vitáková, Martina; Kodym, Petr (Biological psychology, 2003)
Toxoplasma gondii, a parasitic protozoan, infects about 30-60% of people worldwide. The latent toxoplasmosis, i.e. life-long presence of cysts in the brain and muscular tissues, has no effect on human health. However, infected subjects score worse in psychomotor performance tests and have different personality profiles than Toxoplasma-negative subjects. The mechanism of this effect is unknown; however, it is supposed that presence of parasites' cysts in the brain induces an increase of the concentration of dopamine. Here we search for the existence of differences in personality profile between Toxoplasma-positive and Toxoplasma-negative subjects by testing 857 military conscripts using a modern psychobiological questionnaire, namely with Cloninger's Temperament and Character Inventory (TCI). ANCOVA showed that Toxoplasma-positive subjects had lower Novelty seeking (NS) scores (P=0.035) and lower scores for three of its four subscales, namely Impulsiveness (P=0.049), Extravagance (P=0.056) and Disorderliness (P=0.006) than the Toxoplasma-negative subjects. Differences between Toxoplasma-negative and positive subjects in NS was inversely correlated with duration of toxoplasmosis estimated on the basis of concentration anti-Toxoplasma antibodies (P=0.031). Unexpectedly, the infected subjects had also lower IQ (P(2)=0.003) and lower probability of achieving a higher education (P(2)<0.0000). Decrease of NS suggests that the increase of dopamine in brain of infected subjects can represent a missing link between toxoplasmosis and schizophrenia.
Keywords: protilátky protozoální; Male; Brain; Schizophrenia; Adult; Antibodies, Protozoan; dospělí; toxoplazmóza; mužské pohlaví; dopamin; Schizophrenic Psychology; Dopamine; testování osobnosti; Exploratory Behavior; Intelligence; schizofrenie (psychologie); lidé; Toxoplasmosis; Humans; inteligence; schizofrenie; mozek; Personality Assessment; pátrací chování